Compatibility of recombinant tissue plasminogen activator (rtPA) and aflibercept or ranibizumab coapplied for neovascular age-related macular degeneration with submacular haemorrhage. Issue 6 (4th March 2015) - Klettner, Alexa; Grotelüschen, Simon; Treumer, Felix; Roider, Johann; Hillenkamp, Jost
Abstract : Background/aims: Subretinal coapplication of recombinant tissue plasminogen activator (rtPA) and vascular endothelial growth factor (VEGF)-antagonists is a new treatment option for age-related macular degeneration complicated by submacular haemorrhage. Here, we investigate the compatibility of rtPA and aflibercept or ranibizumab in vitro because intraoperatively, rtPA or rtPA-induced plasmin may cleave aflibercept or ranibizumab. Methods: Aflibercept and ranibizumab, respectively, were incubated with rtPA or plasmin, separated in gel electrophoresis and stained with Coomassie or silver. The antiangiogenic activity of the VEGF-antagonists was quantified by VEGF-ELISA after incubation with the supernatant of primary porcine retinal pigment epithelium cell cultures. Results: In electrophoresis, ranibizumab displayed no additional fragments when it was coapplied with rtPA or plasmin. Its VEGF-inhibiting efficacy remained unchanged in coapplication with rtPA with or without blood, or plasmin. rtPA did not cleave or functionally compromise aflibercept. When aflibercept was coapplied with plasmin, electrophoresis displayed additional bands in Coomassie (30 kDa, 27 kDa, 19 kDa, 15 kDa) and silver staining (31 kDa, 26 kDa, 21 kDa, 19 kDa, 15 kDa). While at a clinical dosage (800 µg/mL) VEGF was inhibited by aflibercept when coapplied with plasmin, at borderline concentrations (400 ng/mL) VEGF-binding ability of aflibercept was abolished. Conclusions: Ranibizumab is not cleaved or functionally compromised by rtPA or plasmin. Aflibercept is cleaved and its VEGF-binding ability is reduced when coapplied with plasmin. In clinical practice, rtPA and ranibizumab can be coapplied as a treatment for neovascular age-related macular degeneration with submacular haemorrhage while the antiangiogenic activity of aflibercept may be compromised when coapplied with rtPA in the presence of plasmin.